60 Obesity in Older Adults in the Epic Norfolk Study is Associated with Reduced 20-Year Falls Hospitalization. (20th December 2019) - Kioh, Sheng Hui; Sumaiyah, Mat; Myint, Phyo; Tan, Maw Pin
Abstract: Background: One in three older adults fall each year leading to increased disability, hospitalizations and mortality. Recent studies suggested an increased risk of falls among obese individuals which may correlate with increased rates of falls hospitalizations. However, there is not much information supporting the hypothesis that obesity may influence the risk of falls related hospitalizations. Aims: To prospectively investigate whether body mass index (BMI) is a predictor for falls hospitalization by age group in the population of the EPIC-Norfolk Study. Methods: Body height and weight were measured at baseline and BMI calculated. Falls hospitalization status over 20 years' follow-up was ascertained using data linkage with centralized NHS records. Participants were categorized into the four BMI groups: underweight (BMI <18.5kg/m 2 ), normal (18.5 ≤ BMI < 25.0 kg/m 2 ), overweight ( 25.0 ≤ BMI < 30.0 kg/m 2 ) and obese ( BMI ≥ 30.0kg/m 2 ), and according to three age groups ( < 55 years, 55-64 years, ≥ 65 years). Results: Data from 25636 individuals, (54.7%) women and (45.3%) men, mean age 59.2 ± 9.3 years, were included. For individuals within the under 55-year age group at baseline, individuals who were overweight (HR = 1.25; 95% CI= 1.01-1.56) and obese (HR = 1.54; 95% CI= 1.17-1.81) were at higher risk of falls hospitalization compared with those with normal BMI. As for individuals aged ≥ 65 years at recruitment, individuals who were obese were less likely to be hospitalized after a fall (HR = 0.85; 95% CI= 0.74 – 0.97) compared to those with normal BMI. Conclusions: The relationship between obesity and falls hospitalization over 20 years differed between those aged <55years and 65years, with an increased risk observed for those <55years and reduced risk in those 65years. The underlying rationale for this finding will need to be evaluated in future studies.